2017
DOI: 10.1002/2017ja024484
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Proton Spectra Measured by the Van Allen Probes

Abstract: We test the hypothesis that pitch angle scattering by electromagnetic ion cyclotron (EMIC) waves can limit ring current proton fluxes. For two chosen magnetic storms, during 17–20 March 2013 and 17–20 March 2015, we measure proton energy spectra in the region 3 ≤ L ≤ 6 using the RBSPICE‐B instrument on the Van Allen Probes. The most intense proton spectra are observed to occur during the recovery periods of the respective storms. Using proton precipitation data from the POES (NOAA and MetOp) spacecraft, we ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The level 3‐PAP data with pitch angle information are adopted in this study. Due to the high‐voltage issues during the early phase of the emission of RBSPICE‐A, we only adopted the data from RBSPICE‐B in the present study (Summers et al., 2017). To ensure the reliability of the RBSPICE TOFxE product used in this study, we have replaced the data of the lowest energy channel from the TOFxE product with that of a similar energy channel from the TOFxPHHELT product (personal communications with Martina Gkioulidou).…”
Section: Instrumentation and Data Setsmentioning
confidence: 99%
“…The level 3‐PAP data with pitch angle information are adopted in this study. Due to the high‐voltage issues during the early phase of the emission of RBSPICE‐A, we only adopted the data from RBSPICE‐B in the present study (Summers et al., 2017). To ensure the reliability of the RBSPICE TOFxE product used in this study, we have replaced the data of the lowest energy channel from the TOFxE product with that of a similar energy channel from the TOFxPHHELT product (personal communications with Martina Gkioulidou).…”
Section: Instrumentation and Data Setsmentioning
confidence: 99%
“…EMIC waves scatter~MeV electrons and~10s-100s keV protons into the loss cone via cyclotron resonance, potentially leading to losses of radiation belt electrons and ring current ions (Cao et al, 2016;Jordanova et al, 2008;Jordanova & Miyoshi, 2005;Li et al, 2007;Meredith et al, 2014;Summers et al, 2017; ©2019. American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Hirai et al () showed direct evidence of correlation between the rising tone EMIC wave structure and the associated bursts of REP. Pitch angle scattering of ring current protons (~10 s of keV) driven by EMIC waves has been often associated with proton aurora (Cao et al, ; Miyoshi et al, ; Summers et al, ; Xiao et al, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%